46.6k views
5 votes
What is the first step in writing f(x)=3x^2+6x-8 in vertex form?

User Mehak
by
4.9k points

2 Answers

3 votes

Explanation:

To convert to vertex form, you need to complete the square. The first step is to factor out the leading coefficient from the first two terms.

f(x) = 3x² + 6x − 8

f(x) = 3 (x² + 2x) − 8

The second step is to take half of the x coefficient, square the result, then add and subtract inside the parentheses. (2/2)² = 1.

f(x) = 3 (x² + 2x + 1 − 1) − 8

Distribute:

f(x) = 3 (x² + 2x + 1) − 3(1) − 8

Factor and simplify:

f(x) = 3 (x + 1)² − 11

User Gilchris
by
4.6k points
7 votes

Answer: factor out 3 from watch terms on edg 2020

Explanation:

User Prashan
by
4.8k points